A Novel Technique for Fabricating Metalized Objects with Difficult Geometries - Powers, Mitchell (Proceedings of the Wisconsin Space Conference, 2012)
In the course of fabricating corrugated horn antennae a technique was developed to avoid certain geometric difficulties. Stereolithograpy, a form of 3D printing, had been employed to create a lightweight, cheap, plastic horn. However, it was found that it was difficult to plate metal into the corrugations of the plastic horn. To work around this, a technique was developed where in the corrugated horn would be produced by assembling a number of easy to plate, interlocking rings. The rings would be plated separately, assembled, and electroplated with an exoskeleton. The general technique could readily be applied to a large number of similarly difficult scenarios.Â